The Effect of Exports and Labor on Economic Growth in North Sulawesi - Ferly Christian Kolinug; Robert Winerungan (AIBPM Publisher, 2022)
The purpose of this study is to analyze the influence of exports and labor on economic growth in North Sulawesi in the last ten years. This study used secondary data taken from the Central Statistics Agency of North Sulawesi for the period 2011–2021. The analysis used was regeresi analysis using an analysis model on the eviews application by taking data on exports, labor and economic growth from the BPS institution of North Sulawesi Province from 2011 to 2021. By testing in the R-Square test model, TestLF and QTYtest, the result is that the export variable has an insignificant influence on the economic growth of north Sulawesi and the labor force has a positive and significant influence on economic growth in North Sulawesi. Keywords: Export, Labor, Economic Growth